Comparative morphology of the snake spectacle using light and transmission electron microscopy. (18th May 2015) - Da Silva, Mari‐Ann O.; Bertelsen, Mads F.; Wang, Tobias; Prause, Jan U.; Svahn, Thøger; Heegaard, Steffen
Abstract: Objective: To determine the interspecific variation in the morphology of the snake spectacle. Animals studied: About 43 snakes of 14 different species, belonging to three different families: Boidae, Colubridae, and Pythonidae. Procedure: The spectacles were examined by light and transmission electron microscopy. The thickness of the stromal layer was measured and the location of the blood vessels was noted. The shape of the transition zone located at the rim of the spectacle and the presence of pigment herein were also recorded. Results: The spectacles of all species examined consisted of three layers. The outer epithelium was made of basal cells with overlaying keratin layers, the stroma comprised layers of organized collagen fibrils, and the inner epithelium was a layer of squamous cells with microvilli. Blood vessels were found in the stroma of all spectacles: in boas and pythons in the middle layers of the stroma and in colubrids adjacent to the inner epithelium. Boas and pythons were endowed with the thickest stromal layers (81–132 μm) compared to colubrids (9–95 μm). Boas and pythons had a convex transition zone, while the transition zone of the colubrids exhibited a steady increase in spectacle thickness toward the hinge region. The transition zone contained pigment in boas and pythons. Conclusion: The overall morphology of the spectacle was similar among the major families of snakes. However, the location of blood vessels and appearance of transition zone differed, as did the overall thickness of the spectacle.